A study of large-scale vertical motion over West Africa - JEGEDE, OLUWAGBEMIGA O. (MAUSAM, 1992)
Three separately recorded cases of thundery weather over West Africa that occurred during the conduct of the West African Monsoon Experiment (WAMEX) of 1979, are investigated with the kinematic vertical p-velocity field. The scheme employed here is based on a least-squares-plane technique which has been desribed in Jegede and Balogun (1991), as a variant to the similar methods used by Kung (1972, 1973), and Pedder (1981). The aim in this study is to demonstrate the practicability of the kinematic method for interpreting observed surface weather. In all the three cast-s, there was some consistency noted between the precipitation patterns and the computed vertical velocity fields within the sub-region.